Colonial Vestiges, Indigenous Policy-Logical-Framework, and Sustainable Development in Nigeria - Samuel O. Okafor (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2022)
Countries in Africa continue to represent practical examples of failed nation-states due to the persistence of all known indicators of underdevelopment.  Ironically, the continent has a proud social history that eulogizes its contribution to global development. However, a careful look at most of the countries (such as Nigeria) that make up the continent reveals an image of adverse human development realities. This negative socio-economic scenario has put the continent at the forefront of foreign aid destinations even though Africa has all it takes to drive a healthy development agenda. The manner with which development policies are far removed from the reach of the masses in terms of their input, needs, and aspirations, shows the nature of the colonial character that surrounds policymaking in a country like Nigeria. It is the submission of this paper, that decolonizing policy-making processes and ensuring that the masses are integrated into the process would go a long way to synthesize the indigenous aspirations, elite groups, and valid experience for sustainable development. Hence, using the colonial policy template diagram and the post-colonial policy template diagram of successive governments, the paper evaluated the structure of policymaking and implementation in Nigeria and the disconnection between policy objectives and realities in the economy. Based on the findings, the paper recommends an indigenous and populist informed policymaking process to reverse the colonization of development policies in Nigeria and to engender a sustainable development policy trajectory.